The Implementation of Digital Technology to Enhance Energy Business Sustainability Through Operational Performance Improvement - Saputro, Adi; Riyadi, Selamet; Lestari, Setyani Dwi; Muhdaliha, Eryco; David, David (Pt. Anagata Sembagi Education, 2024)
This study investigates the role of digital technology in improving business sustainability in Indonesia's energy sector, focusing on its impact on operational performance. The study aims to investigate how the adoption of digital tools such as automation, smart grid, and data analytics can help improve energy efficiency, reduce operational costs, and promote sustainable business practices. The study takes a quantitative approach and uses SPSS for data analysis to assess the impact of digital technologies on energy companies' operational performance and sustainability. The results show that there is a significant positive correlation between the adoption of digital technologies and both operational performance and business sustainability. These findings suggest that the integration of digital tools can lead to more efficient energy management, reduced costs, and improved sustainability practices in the energy sector. The study provides valuable insights for energy companies and policymakers, offering practical recommendations to aid in the adoption of digital technologies and further promote sustainability efforts in Indonesia's energy industry.